Interpersonal Communication of Islamic Religious Education Teachers in Improving Students' Learning Ability - Nabilah Ramadhani; Faridah Faridah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Effective interpersonal communication by teachers supports learning through empathetic, argumentative, and ethical verbal and nonverbal approaches, building students’ motivation, trust, and engagement in an inclusive learning environment. This study aims to understand the interpersonal communication of Islamic Religious Education teachers in establishing positive relationships to support students' academic success. This research uses a qualitative descriptive approach with a case study design to explore interpersonal communication between Islamic Education teachers and students through participatory observation, in-depth interviews, and documentation. Data were analyzed using the Miles, Huberman, and Saldana method, which includes data reduction, presentation, and conclusion drawing. Data validity was maintained through source and method triangulation, member checking, and peer discussions. The results indicate that teachers’ interpersonal communication strategies involve a harmonious blend of verbal and nonverbal communication. Teachers deliver material through lectures, advice, and praise, while reinforcing messages with facial expressions and gestures. Values such as empathy, openness, support, positive attitudes, and equality form the foundation for building strong emotional connections with students. Supporting factors such as extended learning time and school programs also strengthen communication. Despite challenges like large class sizes and negative student perceptions, adaptive and empathetic strategies successfully create a positive and inclusive learning atmosphere. Conclusion: The interpersonal communication strategies of teachers enhance learning through verbal and nonverbal approaches that foster closeness, participation, and a positive atmosphere.